2002
DOI: 10.1029/2001jd001539
|View full text |Cite
|
Sign up to set email alerts
|

Summertime nitrous acid chemistry in the atmospheric boundary layer at a rural site in New York State

Abstract: [1] Ambient measurements of HONO and HNO 3 , using a highly sensitive coil scrubbing/ HPLC/visible detection technique, were made at a rural site in southwestern New York State from 26 June to 14 July 1998, along with concurrent measurements of NO x , NO y , O 3 , and various meteorological parameters. The mean (and median) half-hour concentrations of HONO and HNO 3 during this period were 63 (and 56) pptv and 418 (and 339) pptv, respectively. On average, there were two HONO concentration peaks, the first arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
203
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(224 citation statements)
references
References 32 publications
18
203
3
Order By: Relevance
“…36,38,41,43,47 The measured HONO levels were significantly higher than the values predicted on the basis of the available knowledge about daytime sources and sinks of HONO. The experiments revealed the existence of a strong daytime source of HONO up to 60 times higher than the night time sources 43 and contributing up to 60% to the direct OH radical sources, 48 which was suggested to arise from the photolysis of adsorbed HNO 3 /nitrate 38,47,[49][50][51] or by heterogeneous photochemistry of NO 2 on organic substrates. [52][53][54] Recent work in our laboratory on different aspects of aromatic hydrocarbon photooxidation processes performed in the presence of OH-radical scavengers has revealed that OH radicals are generated during the photolysis of nitrophenols.…”
Section: ð1þmentioning
confidence: 74%
See 1 more Smart Citation
“…36,38,41,43,47 The measured HONO levels were significantly higher than the values predicted on the basis of the available knowledge about daytime sources and sinks of HONO. The experiments revealed the existence of a strong daytime source of HONO up to 60 times higher than the night time sources 43 and contributing up to 60% to the direct OH radical sources, 48 which was suggested to arise from the photolysis of adsorbed HNO 3 /nitrate 38,47,[49][50][51] or by heterogeneous photochemistry of NO 2 on organic substrates. [52][53][54] Recent work in our laboratory on different aspects of aromatic hydrocarbon photooxidation processes performed in the presence of OH-radical scavengers has revealed that OH radicals are generated during the photolysis of nitrophenols.…”
Section: ð1þmentioning
confidence: 74%
“…[36][37][38][39][40][41][42][43] While the night time formation of HONO in the atmosphere is reasonably well explained by direct emissions and different heterogeneous conversion processes of NO 2 [44][45][46] on ground surfaces, 42 recent sensitive measurements have shown unexpectedly high HONO concentrations during the daytime. 36,38,41,43,47 The measured HONO levels were significantly higher than the values predicted on the basis of the available knowledge about daytime sources and sinks of HONO. The experiments revealed the existence of a strong daytime source of HONO up to 60 times higher than the night time sources 43 and contributing up to 60% to the direct OH radical sources, 48 which was suggested to arise from the photolysis of adsorbed HNO 3 /nitrate 38,47,[49][50][51] or by heterogeneous photochemistry of NO 2 on organic substrates.…”
Section: ð1þmentioning
confidence: 99%
“…Many studies focussed on the reduction of NO 2 involving organic photosensitizers like hydrocarbons on soot (Monge et al, 2010) or humic acids (Stemmler et al, 2006(Stemmler et al, , 2007. As already proposed from smog chamber experiments (Killus and Whitten, 1990), photolysis of deposited HNO 3 /nitrate on surfaces was suggested as a daytime HONO source for rural forested environments by Zhou et al (2002aZhou et al ( , b, 2003 and Raivonnen et al (2006). This mechanism is still controversial since the photolysis of HNO 3 was not found to be a photolytic source of HONO in chamber experiments (Rohrer et al, 2005), and quantum yields for HNO 3 /nitrate photolysis are too low in the gas phase and in solution (Kleffmann, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Measured mixing ratios are typically about 1 order of magnitude higher than simulated ones, and an additional source of 200-800 ppt h −1 would be required to explain observed mixing ratios Acker et al, 2006;Li et al, 2012;Su et al, 2008;Elshorbany et al, 2012;Meusel et al, 2016), indicating that estimates of daytime HONO sources are still under debate. It was suggested that HONO arises from the photolysis of nitric acid and nitrate or by heterogeneous photochemistry of NO 2 on organic substrates and soot (Zhou et al, 2001(Zhou et al, , 2002(Zhou et al, and 2003Villena et al, 2011;Ramazan et al, 2004;George et al, 2005;Sosedova et al, 2011;Monge et al, 2010;Han et al, 2016). Stemmler et al (2006Stemmler et al ( , 2007 found HONO formation on light-activated humic acid, and field studies showed that HONO formation correlates with aerosol surface area, NO 2 and solar radiation (Su et al, 2008;Reisinger, 2000;Costabile et al, 2010;Wong et al, 2012;Sörgel et al, 2015) and is increased during foggy periods (Notholt et al, 1992).…”
Section: Introductionmentioning
confidence: 99%